2016
DOI: 10.3892/ol.2016.4195
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardia as a rare symptom of cisplatin cardiotoxicity: A case report

Abstract: Abstract. Cisplatin (DDP) is one of the most frequently used chemotherapeutic agents, and has a characteristic toxicity profile. For DDP, complications affecting the cardiovascular system, which are typical for certain other agents, are rare; however, their occurrence may lead to life-threatening conditions. To the best of our knowledge, there are few reported cases of DDP-induced bradycardia in the relevant medical literature. The current report presents the case of a 58-year-old patient diagnosed with metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
1
14
1
Order By: Relevance
“…Cisplatin-induced bradycardia usually occurs at the very beginning of cisplatin chemotherapy (Altundağ et al 2001;Dieckmann et al 2011;Kounis et al 2016;Kucharz et al 2016). In our experiment, we found similar trend for HR.…”
Section: Discussionsupporting
confidence: 86%
“…Cisplatin-induced bradycardia usually occurs at the very beginning of cisplatin chemotherapy (Altundağ et al 2001;Dieckmann et al 2011;Kounis et al 2016;Kucharz et al 2016). In our experiment, we found similar trend for HR.…”
Section: Discussionsupporting
confidence: 86%
“…It has been in clinical use for more than two decades; however, clinical application of ETP are limited due to its side effects on organs like kidney and heart. Although ETP-induced arrhythmia are very rare (Kridis et al 2013 ), however, it has been reported to induce atrial arrhythmia and infarction especially when combined with cytotoxic drug like cisplatin (Kucharz et al 2016 ; Petrella et al 1989 ). In addition, several case studies also reported myocardial infarction and vasospastic angina in ETP-treated patients (Schwarzer et al 1991 ; Yano and Shimada 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiotoxicity may be an early or late complication after treatment with cisplatin. Acute manifestations are accompanied with electrocardiographic changes and arrhythmias, while late complications are primarily associated with the development of cardiomiopathy and congestive heart failure (12)(13)(14). Experimental evidence supports the hypothesis that cisplatin and its analogues promote cardiotoxicity through the formation of reactive oxygen species (ROS), such as superoxide anion radical (O 2 -.…”
Section: Introductionmentioning
confidence: 95%